Gender differences in mall shopping: A study of shopping behaviour of an emerging nation - M. Sadiq Sohail (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2015)
Fast developments in the food retailing industry have led to growth of shopping malls, particularly in the large cities of Saudi Arabia. The purpose of this study is to compare men and women for differences in mall shopping. Using empirical research, this paper examines differences between the genders associated with mall patronage. Based on a survey of 513 shoppers across Saudi Arabia, the study finds significant differences in shopping behaviour. The paper discusses the findings and makes recommendations to mall operators.
Keywords: M30; M31; M39; M00; 650; gender differences; mall shopping; shopping behaviour; Saudi Arabia